The Effect of Archives Infrastructure and Competency of Archives Officers on the Effectiveness of Work in the Development of Marga and Construction Development of North Sumatra Province - Baskoro Ardi Wibowo; Rudi Salam Sinaga; Maksum Syahri Lubis (Budapest International Research and Critics University, 2021)
The aims of this study to find out the effect of archives infrastructure and competency of archives officers on the effectiveness of work in the development of marga and construction development of North Sumatra Province. The type of research used in this study is a causal relationship research with a quantitative approach. The quantitative approach is a systematic scientific study of the parts and phenomena and their relationships. The result shows that the relationship between the arrangement of archives, infrastructure and the competence of archiving officers on the effectiveness of work in the Department of Highways and Construction of North Sumatra Province that the R Square value obtained is 0.218 or 21.8%. This shows the ability of the Archives Arrangement variable (X1), Infrastructure (X2) and Archive Officer Competence (X3) simultaneously or together to affect Work Effectiveness by 21.8%.